Environmental impacts, exposure pathways, and health effects of PFOA and PFOS - Wee, Sze Yee; Aris, Ahmad Zaharin (Elsevier, 2023)
Per- and polyfluoroalkyl substances (PFAS) are synthetic chemicals that have been widely utilized in various industries since the 1940s, and have now emerged as environmental contaminants. In recent years, perfluorooctanoic acid (PFOA) and perfluorooctane sulfonate (PFOS) have been restricted and replaced with several alternatives. The high persistence, bioaccumulation, and toxicity of these substances have contributed to their emergence as environmental contaminants, and several aspects of their behavior remain largely unknown and require further investigation. The trace level of PFAS makes the development of a monitoring database challenging. Additionally, the potential health issues associated with PFAS are not yet fully understood due to ongoing research and inadequate evidence (experimental and epidemiological studies), especially with regard to the combined effects of exposure to PFAS mixtures and human health risks from drinking water consumption. This in-depth review offers unprecedented insights into the exposure pathways and toxicological impacts of PFAS, addressing critical knowledge gaps in their behaviors and health implications. It presents a comprehensive NABC”Needs, Approach, Benefits, and Challenges”analysis to guide future strategies for the sustainable monitoring and management of these pervasive environmental contaminants.